A Critical Review of Ahmad Nadeem Qasmi Short Story Pawon Ka Kanta Aor Tabar - Neelam,; Hassan, Nadeem (sourcecoder, 2022)
In the early period, Ahmad Nadeem Qasmi was a supporter of the fact that writing is essential for the creator to reflect the environment in which he grew up, because those who spend day and night in the dust and dirt of the villages cannot imagine that the lights are shining. What darkness is hidden in the light of the cities? Similarly, those who are robbed of the pleasures of the comfortable life of the city cannot realize that what the name of deprivation and helplessness is. However, going forward, this limit of time and space Bandi disliked his art. So he covered cities and the world scene with villages. A positive aspect of his personality is that he is a good poet and an excellent fiction writer at the same time. They use their poetic skills for their fictional style, and wherever they feel the need in poetry and poetry, they use their art of fiction writing. This is the reason that neither their idea is a copy of anyone. And the style is not borrowed from anyone. Rather, whatever is, is pure and theirs. He has based his opinion on personal experiences and observations. That's why they see pictures of life. They get into the characters of each of their fictions and get to understand the real truths.